Role of Mitral Annular Systolic Velocity in The Evaluation of Left Atrial Appendage Function in Mitral Stenosis (Cardiovascular Journal, 2011)
Background : Mitral stenosis (MS) is the most common valvular heart disease. Thromboembolism is one of the most important complications of MS, especially when it is associated with atrial fibrillation (AF).Patients with sinus rhythm (SR) are also sussceptible to this complication when it is associated with left atrial appendage (LAA) dysfunction .LAA dysfunction is an independent predictor of thromboembolism in mitral stenosis. Objectives: To investigate whether there is a relation between mitral annular velocities obtained by Doppler tissue imaging (DTI) and LAA function determined by transoesophageal echocardiography (TEE) and to determine if the annular velocities can predict the presence of the inactive LAA in MS. Methods: Sixty MS patients were evaluated by transthoracic echocardiography and all patients underwent transesophageal echocardiography. The annular systolic (S-wave) and diastolic (Emand Am-waves) velocities were recorded. Inactive LAA was defined as LAA emptying velocity